The study of lateral torsional buckling behaviour of beam with trapezoid web steel section by experimental and finite element analysis - Denan, Fatimah (Academic Research Publishing Agency, 2010)

(untitled)
Experimental and numerical study on lateral torsional buckling behaviour of steel section with trapezoid web is presented in this paper. Comparison is made with conventional beams with flat web. In the experimental work, sections with nominal dimension 200 x 80 mm and 5 m length were loaded vertically while the lateral deflection were unrestrained to allow for the lateral torsional buckling. In the analytical study, eigen-value buckling analysis in the finite element method was used to determine the critical buckling load. It is concluded that steel beam with trapezoidally corrugated web section have higher resistance to lateral torsional buckling compared to that of section with flat web. The result shows that corrugation thickness influence the resistance to lateral torsional buckling.